Hubungan Kebiasaan Belajar pada Masa Pandemi Covid-19 terhadap Prestasi Belajar Kimia Siswa Kelas X SMA Negeri di Kabupaten Kutai Barat - Meri; Kusumawardhani, Ratna; Widiyowati, Iis Intan (LPPM Universitas Negeri Jakarta, 2023)
Abstract This study aims to determine the relationship between study habits during thepandemic COVID-19and the chemistry learning achievement of class X State Senior High School students in West Kutai Regency. The population used was all X grade students from three public high schools in West Kutai Regency consisting of SMAN 1 Linggang Bigung, SMAN 1 Long Iram and SMAN 2 Sendawar with non- probability sampling using purposive sampling method and obtained a sample of 129 students. The instrument used was a study habit questionnaire. This type of research isresearch ex past facto. Data analysis used descriptive statistics and inferential statistics, namely simple linear regression analysis with a significance level of 5%. Based on the results of descriptive data analysis, it was obtained that students' study habits were in the medium category with a percentage of 35.66% and student achievement variables were in the medium category with a percentage of 31.78%. From the results of inferential analysis using simple linear regression, the t-test obtained a significance of 0.583 > 0.05, indicating that there is no relationship between study habits and academic achievement in class X State Senior High School Students in West Kutai Regency. Keywords Study Habits, Chemistry Study Achievement, COVID-19.